Best Available Evidence or Truth for the Moment: Bias in Research. (January 2022) - Florczak, Kristine L.
The subject of this column is the nature of bias in both quantitative and qualitative research. To that end, bias will be defined and then both the processes by which it enters into research will be entertained along with discussions on how to ameliorate this problem.